ASSESSING EFL LEARNERS' MASTERY OF SIMPLE PRESENT AND PRESENT PROGRESSIVE TENSES - Epa, Yulma; Utami, Elva; Yuneva, Yuneva; Kencana, Nila; Anwar, Eka Nurdianty (JOEEL (Journal of English Education and Literature), 2025)
This study explores the mastery of the simple present and present progressive tenses among second-semester Counseling Guidance students at Universitas Prof. Dr. Hazairin, SH, Bengkulu. The purpose of the study is to assess students ability to use these tenses correctly in both written and spoken forms. A mixed-methods approach was employed, consisting of a grammar test to evaluate students' written proficiency and structured interviews to assess their spoken usage. The results revealed that while students showed relatively high proficiency in using the simple present tense, their performance with the present progressive tense was weaker. Common errors identified included confusion between the two tenses, omission of auxiliary verbs, and incorrect verb forms. These findings suggest that students have a solid grasp of the simple present tense but face difficulties with the present progressive tense, largely due to the absence of similar tense forms in their native language. The study concludes that targeted grammar instruction, particularly focused on the present progressive tense, is essential. It also recommends incorporating task-based learning and form-focused instruction to enhance grammatical accuracy. The findings offer valuable insights into tense acquisition among Indonesian EFL learners and have implications for improving English grammar teaching practices at the university level.